DOP078 Visceral and subcutaneous adipose tissues of Crohn's disease patients contains bacteria. (16th January 2018) - Serena, C; Terrón-Puig, M; Maymó-Masip, E; Queipo-Ortuño, M; Sabadell-Basallote, J; Rodríguez, M M; Nuñez-Roa, C; Menacho, M; Espin, E; Zorzano, A; Millan, M; Fernández-Veledo, S; et al.
Abstract: Background: In recent years, a greater appreciation for the microbes inhabiting unexpected tissues of the human body has emerged. Their properties are both harmful and beneficial to health. It is largely accepted that the intestinal microbiota is involved in the onset of Crohn's disease (CD). Indeed, a reduced immune tolerance to components of the intestinal commensal microbiota and inflammation of the intestinal barrier typifies patients with CD. Hyperplasia of the mesenteric adipose tissue (AT) adjacent to the inflamed regions of the intestine, so-called creeping fat (CF) is a hallmark of CD and seems to be directly related to disease activity. We hypothesise that mesenteric AT might cooperate with the gut in a pro-inflammatory feedback loop generating a specific microbiota signature in this tissue, influencing CD outcome and disease progression. Methods: Using 16S rRNA sequencing and culture, we analysed AT microbiota from different AT compartments (CF, healthy mesenteric (hMES) and subcutaneous) of 10 active and 10 inactive CD subjects matched by gender, body mass index (BMI) and age. Donors are being recruited at Hospital Joan XXIII of Tarragona and Hospital Vall d'Hebron of Barcelona in accordance with the principles of the Helsinki Declaration. Results: Microbiota have been discover recently in some unexpected tissues in humans. Interestingly, using 16S RNA sequencing we observed that the family richness index increase significantly in visceral fat depots compared with subcutaneous fat depots (Figure 1A). To note, the relative abundance (RA) of Enterobacteriaceae dramatically increases in viceral fat depots (both origins CF and hMES) (Figure 1B) accordingly to those found increased in faeces and intestinal mucosa of CD patients. At species level, Escheriachia coli is the most abundant bacteria in VAT (CF and hMES) of CD patients. Curiously, inactive CD have a significant reduction in the RA of Enterobacteriaceae compared with active CD patients. Remarkably, we were able to culture living bacteria within AT in CD subjects (Figure 1C). Conclusions: This research shows that AT in humans is not sterile but contains a diverse community of bacteria, adding to the literature that body sites once believed to be sterile do indeed have an endogenous microbiome at least in disease such as CD. Further studies are required but the goal in CD subjects may be to develop an effective personalised treatment based on knowledge of the individual's microbiota profile (both gut and adipose tissue microbiota).